Scientific Exchanges between France and Brazil in the History of Psychology. The Role of Georges Dumas between 1908 and 1946 - Bandeira de Melo, Carolina S; École de Hautes Études en Sciences Sociales and the Faculdade de Educaçao da Universidade Federal de Minas Gerais. Scholarship from CAPES (2014)
This article presents the role of Georges Dumas in the development of Brazilian psychology in the first half of the twentieth century. France had at that moment a major influence on Brazilian cultural and scientific development, including the field of psychology. Georges Dumas had a prominent presence in Brazil, acting as a gatekeeper when choosing French scholars to give conferences and classes in Brazil between 1908 and 1940 as a representative of the French cultural tradition. The bibliography of Georges Dumas’s Traité de Psychologie, published in 1922-1923, shows a selection of Brazilian scholars who interacted with the author 1900’s ans 1940’s. The political context of French-Brazilian exchanges and the names of professors involved in the French mission in Brazil in the field of psychology were studied. The French cultural influence in Brazil is interpreted as a strategy aimed at contributing to the solution of Brazilian problems, and it helped to change the image of Brazil in Europe. In addition, scientific exchanges promoted the extension of the French diplomatic network.